Comparison of Apical Debris Extrusion Using EDDY, EndoActivator, Ultrasonic Irrigation and Manual Dynamic Agitation - Mirze Muhammet Özen; Oğuzhan Ünal; Mine Büker; Meltem Sümbüllü (Current Research in Dental Sciences)
Objective: This study was aimed to determine the amount of apically extruded debris using different final irrigation activation techniques.Methods: The mesial roots of 70 extracted mandibular molar teeth were included. The mesiobuccal roots were instrumented to size 40/.06 with a reciprocal system file and divided into five groups according to the final irrigation activation technique used: EDDY, EndoActivator (EA), passive ultrasonic irrigation (PUI), manual dynamic agitation (MDA) or needle irrigation (NI). The extruded debris was collected in Eppendorf tubes and stored in an incubator at 70°C for 5 days. The results were analysed using the Kruskal–Wallis test (P=.05).Results: EDDY and the EA caused significantly more apical debris extrusion (P < .05). There were no statistically significant differences between EDDY and the EA (P > .05). NI caused less extrusion, but there were no statistically significant differences between PUI, MDA and NI (P > .05).Conclusion: EDDY and the EA were associated with significantly higher apical extrusion debris extrusion.Keywords: debris extrusion, EDDY, Endoactivator, irrigation activation, manual dynamic agitation, ultrasonic irrigation.